Estudo da prevalência da hipertensão arterial e sua associação com alguns fatores de risco em adultos de uma cidade de pequeno porte do interior do Brasil - NASCENTE, Flávia Miquetichuc Nogueira (2009)
Hypertension is one of the biggest problems of public health all over the world. It s a common disease, asymptomatic, readily detectable, usually easy to treat and often generates lethal complications when it s not treated. Some risk factors for this disease are common, even in small urban nucleus. OBJECTIVE To estimate the prevalence of hypertension and its correlation with some cardiovascular risk factors in adult population from Firminópolis Goiás. METHODS - This was a descriptive, observational, transversal population-based study substantiated by the home survey of a simple random sample (≥18 years old). Standardized questionnaires were used, blood pressure (BP) measures (Hypertension BP ≥ 140x90mmHg), weight, height, Body Mass Index (BMI) and Abdominal Circumference (AC) were performed. Microsoft Access and Epi-Info 3.3.2 were used for data storage and analysis, respectively. RESULTS The study evaluated 1.168 individuals. There was a predominance of females (63,2%), mean age 43,2 ± 14,9 years old. Overweight prevalence was 33,7% and obesity 16,0%. Abdominal Circunference changed in 51,8% (24,2% high risk and 27,7% very high risk). The prevalence of smoking was 23,2%, more frequent among males (27,3%) when compared to females (20,8%). A sedentary lifestyle was observed in 67,6% females and 64,8% males. Regular alcohol consumption was reported by 33,3% of the sample, with the predominance of males. The prevalence of Hypertension was 32,7%. It was found a positive correlation among Hypertension, BMI, AC, age and negatively with schooling. CONCLUSION It was found a high prevalence of Hypertension, overweight, obesity and abdominal circumference. Anthropometric data over appropriate values and age increase the risk for hypertension, while the number of years of study and female gender represented a protective factor for its occurrence